Perancangan Aplikasi Perpustakaan Berbasis Dekstop di Sekolah dengan Menggunakan Metode Waterfall - Endar Nirmala; Ahmad Darmawan; Ersa Putri Muharom; Fitri Anis Isroriyah; Marjuki Marjuki; Teti Desyani (Teknik Informatika Universitas Pamulang, 2022)
This Library System aims to facilitate the process of exploiting data and information in the library and to increase student reading interest. The library at school there are various books that can help the learning process. At this time in data processing in the library still using a manual system. The purpose of this library application is designed for optimal service so that the data stored is very accurate and makes it easier for admins to process data. In this Library Information System uses the waterfall method which is a classic method that is systematic sequentially in building software from the beginning of the analysis, design, coding, testing and maintenance stages. Tools used for software modeling use unified modeling language (UML) such as use case diagrams. This library application can be used by admins / library staff and students. Library admins can use this library application to process books, procure books, lend books, and manage reports. Meanwhile, students can use this library application to fill in member visits, book searches, and borrow books from the library. Thus, library applications can make it easier for admins in the data processing process so that book lending transactions will also be more effective and efficient so that errors in data processing can be reduced.